N/A Communication Barriers: Effects on Natural Disaster Preparedness - Asenas, Rodalin Nalzaro (IJRDO- Journal of Educational Research, 2018)
Abstract This study aimed to analyze the communication barriers like language differences, cultural differences and low safety literacy that affect natural disaster preparedness in order to determine the individual’s capability of taking action and overcoming from tremendous natural phenomena. Since effective communication is vital to the wellbeing and protection of an individual, it requires understanding. Without it, effectual communication can’t be possible; as effectual communication is missing, the condition of providing protection and care ends—or everything becomes meaningless, worthless, and hazards to everyone’s wellbeing. Therefore the individual’s ability, to speak and comprehend English language, plays essential role in this study. This is a descriptive research design utilizing survey questionnaire. Descriptive statistics using frequency distribution, percentage, mean, standard deviation, averaging and descriptive ratings based on 5-point scale were utilized. On the extent of communication barriers’ effects on natural disaster preparedness, language differences and cultural differences were both perceived as great extent, while moderate extent was the descriptive rating for low safety literacy and others (personal related factors), respectively. This portion points out that when language or cultural interferences are recognized, we often bother whether a person comprehends oral or written communication. Nevertheless, if those involved in communication use the same language and experience the same culture, understanding is expected. However, there are groups of people who are functionally illiterate: the absence of reading and writing, they just know the safety instructions by themselves. In the light of the foregoing finding and conclusion, the following were recommended: The individual must enhance his/her capacity to communicate as it served as the most important vehicle to keep abreast of the information required in his/her work assignment. Because many employees have significant family responsibilities, it is important that management considers workers’ situations and advise them to keep always their life safe, work manageably and conform to natural disaster preparedness. Because communication is more than a cognitive process, research suggests that education must highlight its significant role of improving the capacity of individuals and communities to reduce the risk of natural disasters. As a result, activities such as anticipating, educating and informing will be given priority. The Higher Education administration must strengthen community engagement services through seminar/training/workshop dealing with communication deficiency and other activities which can foster positive and supportive communication enhancement in the community.